Financial Knowledge Financial Attitudes and Personality as Key Determinants of Financial Management Behavior Among Young Adults - Michelle Phang; Tannia Tannia; Elkunny Dovir Siratan; Ferry Novindra Idroes; Hendri Setiadi (DINASTI RESEARCH, 2026)
This study examines determinants of financial management behavior among Indonesian youth aged, a productive cohort that is central to economic resilience yet faces persistent challenges in budgeting, saving regularity, and long-term planning. Building on behavioral finance perspectives, the framework integrates financial knowledge, financial attitude, and personality to address a documented research gap in Indonesian youth contexts where cognitive explanations are often examined without sufficient integration of affective and psychological factors. Using a quantitative survey design with a five-point Likert scale, data were collected from 435 purposively selected respondents meeting criteria related to age, residence, income/allowance, and active financial management experience. Data were analyzed in SPSS (v25) through instrument testing and multiple regression procedures (validity, reliability, t-test, F-test, and model fit indices). The result is intended to inform youth-focused financial education and policy initiatives by emphasizing integrated interventions that strengthen literacy, cultivate constructive attitudes, and support self-regulatory development through practical learning.